2022
DOI: 10.1177/10848223211073711
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Pulmonary Diagnoses and Advance Care Planning in Home Health

Abstract: Chronic cardiovascular and pulmonary diseases are prevalent in the US home health population. Heart failure and chronic obstructive pulmonary disease are both chronic and terminal, but they are not always perceived as serious illnesses with imminent death. Therefore, they provide a context for advance care planning that is distinct from the diagnostic contexts of cancer, end-stage renal disease, or dementia. Advance care planning is defined as a process that supports adults at any age or stage of health in und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These current findings are also congruent with our previous finding of 2022 that HHAs with more robust ACP protocols tend to have high percentages of patients with cardiac and pulmonary diagnoses, whose conditions are punctuated by exacerbation events, suggesting that these patients do prefer to use acute care services. 18 Meanwhile, HHAs may refer patients with other serious illnesses to other services in line with their goals and treatment preferences that do not include acute care services. 17 Together, the 3 studies suggested that HHVBP agencies with robust ACP protocols were associated with higher hospitalization rates, higher ED use rates, and higher proportions of patients with cardiac and pulmonary diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…These current findings are also congruent with our previous finding of 2022 that HHAs with more robust ACP protocols tend to have high percentages of patients with cardiac and pulmonary diagnoses, whose conditions are punctuated by exacerbation events, suggesting that these patients do prefer to use acute care services. 18 Meanwhile, HHAs may refer patients with other serious illnesses to other services in line with their goals and treatment preferences that do not include acute care services. 17 Together, the 3 studies suggested that HHVBP agencies with robust ACP protocols were associated with higher hospitalization rates, higher ED use rates, and higher proportions of patients with cardiac and pulmonary diagnoses.…”
Section: Discussionmentioning
confidence: 99%